Globular C1q Receptor (gC1qR/p32/HABP1) Is Overexpressed in Malignant Pleural Mesothelioma and Is Associated With Increased Survival in Surgical Patients Treated With Chemotherapy - Li, Xiaoyu; Eguchi, Takashi; Aly, Rania G.; Chintala, Navin K.; Tan, Kay See; Zauderer, Marjorie G.; Dembitzer, Francine R.; Beasley, Mary Beth; Ghebrehiwet, Berhane; Adusumilli, Prasad S.; Peerschke, Ellinor I. B. (Frontiers in Oncology, 2019)
Introduction: Globular C1q receptor (gC1qR/p32/HABP1) is overexpressed in a variety of cancers, particularly adenocarcinomas. This study investigated gC1qR expression in malignant pleural mesothelioma (MPM) and its pathophysiologic correlates in a surgical patient cohort. Methods: Tissue microarrays comprising 6 tumoral and 3 stromal cores from 265 patients with MPM (216 epithelioid, 26 biphasic, and 23 sarcomatoid; 1989-2010) were investigated by immunohistochemistry for gC1qR expression (intensity and distribution by H-score, range 0-300), and immune cell infiltration. Overall survival (OS) was analyzed by the Kaplan-Meier method (high versus low gC1qR expression delineated by median score) in the whole cohort and by neoadjuvant chemotherapy (NAC) status. Multivariable Cox analysis included stage, chemotherapy, and immune cell infiltration. Results: gC1qR was overexpressed in all histological types of MPMs (263/265, 99.2%) compared to normal pleura. In epithelioid MPM, high gC1qR expression was associated with better OS (median 25 vs.11 months; p=0.020) among NAC patients, and among patients without NAC (No-NAC) but who received post-operative chemotherapy (median OS 38 vs.19 months; p=0.0007). In multivariable analysis, high gC1qR expression was an independent factor for improved OS in patients treated with NAC. In the No-NAC cohort, high gC1qR expression correlated with lower tumor stage. Moreover, the influence of Ki67 and CD4 T-cell infiltration on OS were more pronounced among patients with high gC1qR expression. Conclusion: This is the first description of gC1qR expression in MPM. The data identify gC1qR as a potential new prognostic factor in patients treated with surgery and chemotherapy.